Binder jet additive manufacturing method to fabricate near net shape crack-free highly dense Fe-6.5 wt.% Si soft magnets. Issue 11 (November 2019) - Cramer, Corson L.; Nandwana, Peeyush; Yan, Jiaqiang; Evans, Samuel F.; Elliott, Amy M.; Chinnasamy, Chins; Paranthaman, M. Parans
Abstract: High silicon (Si) electrical steel has the potential for efficient use in applications such as electrical motors and generators with cost-effective in processing, but it is difficult to manufacture. Increasing the Si content beyond 3 wt.% improves magnetic and electrical properties, with 6.5 wt.% being achievable. The main goal of this research is to design, develop, and implement a scalable additive manufacturing process to fabricate Fe with 6.5 wt.% Si (Fe–6Si) steel with high magnetic permeability, high electrical resistivity, low coercivity, and low residual induction that other methods cannot achieve because of manufacturing limitations. Binder jet additive manufacturing was used to deposit near net shape components that were subsequently sintered via solid-state sintering to achieve near full densification. Here, it is shown that the use of solid-state sintering mitigates cracking since no rapid solidification occurs unlike fusion-based additive technologies. The Fe–6Si samples demonstrated an ultimate tensile strength of 434 MPa, electrical resistivity of 98 μΩ cm, and saturation magnetization of 1.83 T with low coercivity and high permeability. The results strongly supports to replace the only available 0.1 mm thick chemical vapor deposition (CVD) produced Si steel using the cost effective AM method with good mechanical and magnetic properties for motor applications. Abstract : Electromagnetism, Soft magnetic alloy, Fe–6Si, Binder jet additive manufacturing, DC and AC magnetic properties, Stators